The impact of TP53 co-mutations and immunologic microenvironment on outcome of lung cancer with EGFR exon 20 insertions - Christopoulos, Petros; Kluck, Klaus; Kirchner, Martina; Lüders, Heike; Roeper, Julia; Falkenstern-Ge, Roger-Fei; Szewczyk, Marlen; Sticht, Florian; Saalfeld, Felix C.; Wesseler, Claas; Hackanson, Björn; Dintner, Sebastian; et al. (European journal of cancer, 2022)
Background - EGFR exon20 insertions (ex20ins) are targeted by novel compounds in non-small-cell lung cancer (NSCLC). However, data about outcome under conventional therapies and the influence of molecular features are scarce. - Patients and methods - We retrospectively analysed 118 patients with evaluation of radiologic response based on RECIST v1.1. TP53 status was available for 88 cases. - Results - Platinum doublets and chemoimmunotherapy showed similar response rates (20-25%), disease control rates (80%) and median progression-free survival (mPFS, ≈7 months), which were longer compared to monochemotherapy (9%, 59%, 4.1 months), EGFR inhibitors (0%, 46%, 3.0) and PD-(L)1 inhibitors (0%, 30%, 2.1; p < 0.05). Overall survival (OS) was not dependent on the choice of first-line treatment, but related to more lines of systemic therapy (p < 0.05). TP53 mutations and brain metastases were associated with shorter PFS under platinum doublets and EGFR inhibitors (HR 3.3-6.1, p < 0.01), and shorter OS for patients receiving both treatments (p < 0.05). More tumour CD8+ and less Th1 cells were associated with longer OS independent of brain and TP53 status (p < 0.01). No difference in outcome was noted according to the ex20ins site and use of pemetrexed (vs. other cytotoxics) or bevacizumab. Long-lasting responses (>1 year) occasionally occurred under EGFR inhibitors for both ‘near-’ and ‘far-loop’ variants. - Conclusions - Platinum doublets and chemoimmunotherapy have the highest activity with ORR of 20-25% and mPFS of approximately 7 months, regardless of the cytotoxic partner, while PD-(L)1 inhibitors show limited efficacy. TP53 mutations, brain metastases and a lower tumour CD8/Th1-cell ratio are independently associated with shorter survival.
Gesehen am 29.08.2022